2011
DOI: 10.1002/clc.20995
|View full text |Cite
|
Sign up to set email alerts
|

Two Hundred Eight Patients With Apical Hypertrophic Cardiomyopathy in China: Clinical Feature, Prognosis, and Comparison of Pure and Mixed Forms

Abstract: Background: Apical hypertrophic cardiomyopathy (AHCM) is a relatively rare form of hypertrophic cardiomyopathy (HCM), originally described in Japan and later in the West. Limited information is available on this disease in China. Hypothesis: This study was designed to describe clinical features and prognoses of patients with AHCM in China. Methods: A retrospective study of 208 consecutive patients with AHCM examined at FuWai Hospital was performed. Clinical features, mortality, and cardiovascular morbidity wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 33 publications
2
38
0
Order By: Relevance
“…3 In another study 46% of the patients were asymptomatic. 4 In another cohort of 105 patients, 16% complained of angina, 14% had atypical chest pain, 10% had palpitations, 6% complained of dyspnea, and 6% had pre-syncope.…”
Section: Typical Presentationmentioning
confidence: 92%
See 3 more Smart Citations
“…3 In another study 46% of the patients were asymptomatic. 4 In another cohort of 105 patients, 16% complained of angina, 14% had atypical chest pain, 10% had palpitations, 6% complained of dyspnea, and 6% had pre-syncope.…”
Section: Typical Presentationmentioning
confidence: 92%
“…8 AHCM is more commonly classified as "pure" when no concomitant septal hypertrophy is present, and "mixed" when evidence of septal hypertrophy is seen. 3,9 In two studies no significant difference was found between cardiovascular mortality and morbidity between these variants of AHCM. 3,5 Figure 1A and 1B show an illustration of the location of hypertrophy and differences between the two variants.…”
Section: Diagnostic Considerations and Types Of Ahcmmentioning
confidence: 93%
See 2 more Smart Citations
“…Most patients with ApHCM have no symptoms, so they are diagnosed incidentally at an annual health check or a preoperative evaluation [2]. It was initially reported that the typical features of ApHCM consist of a giant negative T wave on an electrocardiogram (ECG) [3], but no giant negative T wave occurs in about 70% of patients with ApHCM, and no negative T wave occurs in about 10% at all [4]. Moreover, evidence of ApHCM cannot be found in some cases with definite negative T waves [5].…”
Section: Introductionmentioning
confidence: 99%